Long-stem Prosthesis for Intertrochanteric and Femoral Neck Fractures in the Elderly: Retrospective Comparison of Short-term Clinical Outcomes - Çağdaş Biçen; Mehmet Akdemir; Mehmet Aykut Türken; Kübra Çekok (Galenos Yayinevi, 2021)
Objective:Hip fracture treatment in elderly patients remains challenging. This study aimed to evaluate short-term clinical results of long-stem cementless arthroplasty in elderly patients with femoral neck and intertrochanteric fractures.Materials and Methods:We collected data of patients we treated with long-stem cementless arthroplasty between January 2011 and December 2019 due to hip fractures. This study included 48 patients (≥65 years of age) with femoral neck and intertrochanteric fractures. The patients underwent either bipolar or total hip arthroplasty. A 2-year follow-up was conducted in all the patients. Outcomes were evaluated with the Harris hip score (HHS), Koval categories, complications and hip and mid-thigh pain. We compared clinical results of patients with femoral neck fractures and those with intertrochanteric fractures.Results:The mean follow-up period was 57 (34-92) months. Sixteen patients had femoral neck fractures and 32 had intertrochanteric fractures. No difference in demographic characteristics and comorbidities was noted between groups. The mean preoperative Barthel index of activities of daily living score was 79. At the last follow-up, the mean HHS of the control group was 77 and the mean Koval categories score was 3. Revision surgeries were conducted in two patients due to dislocation. Infection was observed in one patient and was treated by debridement and anti-biotherapy. Implant loosening and periprosthetic fractures were not noted.Conclusion:With fair outcomes, long-stem cementless arthroplasty is a potential treatment for hip fractures in elderly patients. A longer follow-up to evaluate the efficacy of these prostheses is warranted.